2018
DOI: 10.1016/j.scijus.2017.08.002
|View full text |Cite
|
Sign up to set email alerts
|

Ink dating, part I: Statistical distribution of selected ageing parameters in a ballpoint inks reference population

Abstract: The development of ink dating methods requires an important amount of work in order to be reliably applicable in practice. Major tasks include the definition of ageing parameters to monitor ink ageing. An adequate parameter should ideally fulfil the following criteria: it should evolve as a function of time in a monotonic way, be measurable in a majority of ink entries, be as accurate and reproducible as possible, and finally it should not be influenced too much by transfer and storage conditions. This work ai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(19 citation statements)
references
References 25 publications
2
17
0
Order By: Relevance
“…Very recently, Koenig and Weyermann 18 continued this study and concluded testing seven ageing parameters for ink dating purposes: the phenoxyethanol quantity, relative peak area (RPA), three solvent loss ratios (R%, R%*, NR%) and two solvent loss parameters (R NORM, NR NORM ) -that natural ageing parameters (NR% and NR NORM ) were not suitable ageing parameters for ink entries older than a few weeks. The R% ratio consist of the area of the 2-PE peak, decreased from the area of the 2-PE peak extracted from the same sample which would have been artificially aged, divided by the area of 2-PE and multiplied by 100.…”
Section: Calibration Curve and Linearitymentioning
confidence: 99%
See 2 more Smart Citations
“…Very recently, Koenig and Weyermann 18 continued this study and concluded testing seven ageing parameters for ink dating purposes: the phenoxyethanol quantity, relative peak area (RPA), three solvent loss ratios (R%, R%*, NR%) and two solvent loss parameters (R NORM, NR NORM ) -that natural ageing parameters (NR% and NR NORM ) were not suitable ageing parameters for ink entries older than a few weeks. The R% ratio consist of the area of the 2-PE peak, decreased from the area of the 2-PE peak extracted from the same sample which would have been artificially aged, divided by the area of 2-PE and multiplied by 100.…”
Section: Calibration Curve and Linearitymentioning
confidence: 99%
“…Although the ballpoint pen ink is a complex matrix, the electron impact source of the Mass Spectrometer is able to complete ionize the 2-PE molecule, and in the literature authors until now did not report ionization suppression in GC/MS analysis of 2-PE in pen ink matrix. 12,18,26,27 Because of this, it is reliable to use the curve after injection of standard solutions to determine 2-PE after extraction process.…”
Section: Calibration Curve and Linearitymentioning
confidence: 99%
See 1 more Smart Citation
“…For nearly a century, many studies had been executed by document examiners in all over the world. Some results used to determine the dating of a questioned document were proved to be favorable (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11). Many pathways and methods can be selected for determining the dating of a questioned document.…”
mentioning
confidence: 99%
“…Many methods play an important role in determining the change degree of the material, for example, gas chromatography, liquid chromatography, Raman spectroscopy, thermal analysis, and extraction rate method. The above methods can be employed to determine the age of ballpoint pen ink, iron-based ink, gel pen ink, and jet-printing ink (1)(2)(3)(4)(5)(6)(7)(8)(9)(10)(11).…”
mentioning
confidence: 99%